Pemberdayaan Usaha Kecil Menengah Mikro (UMKM) Berbasis Kemitraan dalam Memodernisasi Alat Bantu Gerak dan Mainan Edukasi - Margiyati Margiyati; Ainnur Rahmanti; Syurrahmi Syurrahmi; Novita Wulan Sari; Diana Dayaningsih; Lilik Sigit W; Dwi Mulianda (BADAN PENERBIT STIEPARI PRESS, 2023)
Partnership-based UMKM assistance is an increasingly important and strategic approach in supporting the development of MSMEs in Indonesia. The interaction of higher education elements will be interesting because it creates mutually beneficial conditions where this can become a source of inspiration for the development of UMKM. This is in line with the scientific vision at STIKES Kesdam IV/Diponegoro which tries to collaborate with several UMKM partners including Ouja Medika and Hakim Edukatif Toys. The aim of this assistance is to develop partners' businesses and realize young entrepreneurial learning for students. Methods of this assistance include Focus Group Discussion (FGD, holding several supporting workshops, organizing work workshops according to work safety culture and arranging permits and expanding product sales networks. The output results of this activity include the production of several product development training modules, social media accounts and e-commerce and business legality with the issuance of NIBs and CVs for both partners.